Inovasi pada Morfologi Motif Parang Batik Tradisional Jawa - Guntur Guntur (PANGGUNG, 2019)
ABSTRACTThis article discusses art innovation, especially the parang motive of traditional Javanese batik. Parang motive innovation seeks to identify changes and developments related to the main motives, inside motives (Javanese: isen), and supporting motives. Parang motif innovations also attempt to identify structural aspects or patterns of composing the primary motives, isen, and supporting motives, and colour-setting patterns. The approach used is comparative morphological parang motifs. Aspects of visual and structural forms of parang motives are compared with one another. The data sources used are the two primary literatures on traditional Javanese batik, which discusses parang motifs. The research results showed that the parang motives of traditional Javanese batik showed changes and developments or innovations. Parang motive innovations occur in the main motive elements, isen motives, and supporting motives. The parang motif innovation also occurs in the processing of parang forms and colouring patterns on fabrics.Keywords: art innovation, morphology, parang motif, Javanese traditional batikABSTRAKArtikel ini membahas tentang inovasi seni, khususnya motif parang batik tradisional Jawa. Inovasi motif parang berupaya mengidentifikasi perubahan dan perkembangan terkait motif utama, motif isian (Jawa: isen), dan motif pendukung. Inovasi motif parang juga berupaya mengidentifikasi aspek struktural atau pola penyusunan motif utama, isen, dan pendukung serta pola penyusunan warna. Pendekatan yang digunakan adalah komparatif morfologis motif parang. Metode penelitian yang digunakan adalah kualitatif dengan sampel sebanyak duabelas motif parang. Aspek bentuk visual dan struktural motif parang diperbandingkan satu dengan yang lain. Sumber data yang digunakan adalah dua pustaka utama batik tradisional Jawa yang membahas tentang motif parang. Hasil penelitian menunjukkan bahwa motif parang batik tradisional Jawa mengalami perubahan dan perkembangan atau inovasi. Inovasi motif parang terjadi pada elemen motif utama, motif isen, dan motif pendukung. Inovasi motif parang juga terjadi pada pengolahan bidang parang dan pola pewarnaan pada kain.Kata kunci: inovasi seni, morfologi, motif parang, batik tradisional Jawa